PLAGIARISM IN THE NET AGE - Badar, Ahmed (Journal of Ayub Medical College Abbottabad, 2003)
Medical writing is a science not art. It is very systematic and has a defined protocol1.There are two types of medical writers, both write under compulsion and both have a phobia of medical writing. The first type is that of researchers, who are involved in some form of research, basic or applied. Every researcher at some stage has to present the work in written form. A person who has done some original work is always willing to present it and remains anxious till the work is published. However it is not necessary that every good researcher is a good writer. The second type is of writers who have to write under compulsion, but have nothing to write about. These are the ones who need publications for promotion or for selection. Be it a post of a registrar in a clinical ward or a promotion to senior professorial appointments, there is a minimum requirement of publications. Everyone is therefore in a rush to publish something. It is this second type mainly that is involved in some sort of fraud. Just about five years back the trend was to insert names into others studies on special requests. Strange combinations of authors from contrasting disciplines were seen in that era. Now a number of authors do not waste time in requesting others for an authorship, nor do they take risk of getting embarrassed by getting their name as author on a paper from some other discipline. The ease in literature review through the net sources has brought a drastic change in the trend. Gone are the days when innovative ideas were published. All what one has to do now is to learn the art of using keywords for a net search. The keywords open the lock of literature. There are abstracts and full text articles available on every discipline and topic. It is very easy to copy an idea or even whole article published in some remote journal of some far flung part of the world, make a few amendments and send it to a journal in some other part of the world. However there is always a risk of being caught. An intelligent person, therefore, collects bits and pieces from different articles to reduce chances of being caught. This amalgam article is even easier to catch as there is no continuity of thoughts. The trend is on the rise. There are a few who are ignorant about the rules for quoting references to other works. These authors are victim to their ignorance about what constitutes the writing and documenting of a paper.2 Out of this ignorance they copy paragraphs upon paragraphs from other studies, although the recommended method is to write the reference in one’s own words and not to copy words of work being referred to. This type of plagiarism is easy to catch as the poor author gives the references of the articles from where the lines have been taken and a good reviewer always can check it. The reputation of medical journals is built over many decades of hard work. The standing depends on the trust of readers.3 The readers start trusting journals only when they feel that the works published are valid and reliable. The editors therefore try to select the best quality original works. The only tool for high quality selection is high quality peer review. A beginner can learn the style and pattern of medical writing from the articles published in standard journals. All the medical journals publish instructions for the authors that contain detailed information about all the components of a medical paper. The international committee of medical journal editors has displayed a comprehensive document on its website (www.icmje.org) that can help everyone in writing quality articles. Nowadays the editors of medical journals see wonderful works being submitted. The methodology is excellent, the presentation is marvelous and there is very little that a reviewer can object upon. The rejection rate of articles at most of the journals is going down. Every article is like a gem and is difficult to reject on the common grounds of statistical or subject review. A general consensus is developing that the improvement in articles is because of increasing awareness about importance of research methodology, biostatistics and medical writing. In my opinion one of the reasons for this sudden increase in the frequency of quality articles is plagiarism, to be exact ’˜intelligent plagiarism’. Plagiarism is ’˜to publish borrowed or copied literary work as original’. Be it ’˜intelligent’ or ’˜ignorant’, plagiarism is a serious ethical violation. Plagiarism can never be eliminated one hundred percent, but the editors and reviewers can reduce it by devising a strategy against it. The manual method is to go through the article carefully. If the author has used ’˜cut’ and ’˜paste’ to create the work then there is no flow of thoughts. This incoherence of thoughts generally raises an alarm in the mind of an experienced reviewer. Such articles must be checked for plagiarism by using proper keywords for net search of matching articles. The net has made plagiarism easy but on the other hand it has made it easy to trace plagiarism.4. The same articles and abstracts that were accessible to the ’˜plagiarist’ are also available to the reviewer. It takes extra effort but using good keywords the net based plagiarism can be easily caught, if not at the time of review on some other day, if not by reviewer then by some reader. The example is an interesting analysis based upon Medline search that found and reported many plagiarized articles in 1998.5 There is an urgent need to recognize the problem of plagiarism in articles submitted to medical journals. The problem is actually bigger than the editors perceive, it is just the tip of iceberg that we are able to see. We have to make decisions at the international level. Peer review has to be revolutionized. We should go beyond checking spellings, methodology, statistical analysis and ethical aspects. There is a need to add relevant points about plagiarism in the checklists for reviewers. There is a need for us to be bold enough to black list authors involved in plagiarism for upto 5 years. There is a need to create a global blacklist that can be displayed at the websites of ’˜World Association of Medical Editors’ (WAME) and ’˜International committee of medical journal editors’ (ICMJE) for reference of all the medical journals in the world. There are a number of softwares being used by universities to catch plagiarism in the students. We must develop software to catch plagiarism in the articles submitted to medical journals. The medical world has already entered into the era of ’˜Evidence Based Medicine’. The medical journals are the source of evidence. If we the editors do not stop plagiarism right now we will be responsible for ’˜Plagiarism Based Evidence’ in the era of ’˜Evidence Based Medicine’.